Association between cognitive function and body composition in older adults: data from NHANES (1999–2002) - Chen, Lianghua; Zou, Liling; Chen, Jingwen; Wang, Yixiao; Liu, Dandan; Yin, Lianjun; Chen, Junqi; Li, Haihong (Frontiers in Aging Neuroscience, 2024)
Aim To investigate the association between cognitive function and body composition in older adults. Methods We collected data on 2080 older adults (>60 years of age) from the National Health and Nutrition Examination Survey (NHANES) for the years 1999–2000 and 2001–2002. Candidate variables included: demographic data (sex, age, race, education level, marital status, poverty-to-income ratio), alcohol consumption, cardiovascular disease, diabetes, osteoporosis, total bone mineral density, and total fat mass. A logistic regression model was established to analyze the association between cognitive function and body composition in older adults. In addition, stratified logics regression analysis was performed by sex and age. Results Bone mineral density significantly affects cognitive function in older adults (p<0.01). When examining the data according to sex, this correlation is present for women (p < 0.01). For men, though, it is not significant (p = 0.081). Stratified by age, total bone mineral density was significantly correlated with cognitive function in 60–70 and 70–80 years old people, but not in older adults older than 80 years(for 60–70 years old, p = 0.019; for 70–80 years old, p = 0.022). There was no significant correlation between total bone mineral density and cognitive function (p = 0.575). Conclusion The decrease of total bone mineral density was significantly correlated with cognitive decline in the older adults, especially among women and older people in the 60 to 80 age group. There was no connection between total fat mass, total percent fat, total lean mass, appendicular lean mass, appendicular lean mass /BMI and cognitive function in the older adults.